(untitled) (Architecture Image Studies, 2025)
This study aims to analyze the factors that influence faculty turnover intention at Muhammadiyah Universities (PTM) in the Greater Jakarta area. The independent variables include Work Ethics, Quality of Work Life (QWL), Digital Literacy, Motivation, Employee Engagement, and Career Development, with Job Satisfaction as the intervening variable and Work Experience as the moderating variable. The research uses a quantitative method with a survey approach of 340 lecturers selected through purposive random sampling. Data analysis was performed using Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The results show that Work Ethics, QWL, Digital Literacy, Motivation, and Career Development have a significant positive effect on Job Satisfaction. However, Employee Engagement does not have a significant effect on Job Satisfaction. Meanwhile, some independent variables, such as Work Ethics and Career Development, also have a significant effect on turnover intention. Job Satisfaction was found to mediate some of the relationships between variables. Work Experience does not moderate the relationship between Career Development and turnover intention. This study emphasizes the importance of balanced management of internal lecturer factors, including job satisfaction, to reduce the level of turnover intention at PTM.